ORGANOCHLORINE PESTICIDE RESIDUES ON THE HORTICULTURAL LAND OF THE BANDUNG REGENCY, INDONESIA: ASSESSMENT OF SPATIAL DISTRIBUTION AND HUMAN HEALTH RISKS - Sukarjo Sukarjo; Hidayatuz Zu'amah; Cicik Oktasari Handayani (Universitas Airlangga, 2022)
Introduction: Agricultural land in the Bandung Regency, particularly horticultural land, is contaminated with organochlorine pollutants. This research aimed to determine the extent of organochlorine contamination, acute and carcinogenic health issues, and their spatial distribution. Methods: The study was undertaken by collecting 163 tillage-layer soil samples. The sampling site was determined using the 1.3 x 1.3 km grid method. Using the QuEChERS method, soil samples were extracted, and the residual amounts of endosulfan, dieldrin, and chlordane were determined using GC-MS. Results and Discussion: Endosulfan, dieldrin, and chlordane residual levels in the soil were determined to be 0.00463, 0.00935, 0.01509, 0.02295, and 0.14432, 0.18602 mg/kg, respectively. Acute health risks for adults and children indicate that unfavorable non-cancerous health outcomes are unlikely. For adults, the overall lifetime cancer risk is 12.27% very low risk, 87.12% low risk, and 0.61% moderate risk. The total lifetime cancer risk for children is 8.59% very low risk, 90.18% low risk, and 1.23% moderate risk. Conclusion: The presence of the three organochlorine residues discovered in agricultural soil samples does not threaten human health, but research is still needed on organochlorine residues as a whole.